Emerging neuromodulation treatments for opioid and stimulant use disorders - Howard, Susanna D.; Qiu, Liming; Hager, Nathan; Childress, Anna Rose; Halpern, Casey H.; Scangos, Katherine W. (Frontiers in Human Neuroscience, 2025)
Over the past decade, deaths attributable to opioid and stimulant use have risen dramatically. While the U.S. Food and Drug Administration (FDA) has approved three medications for opioid use disorder, there is currently no FDA-approved treatment for stimulant use disorder. Despite the availability of medications for opioid use disorder, the rates of relapse and overdose, particularly in the time of widespread fentanyl use, remain distressingly high. There is an urgent need for more effective treatment options for these debilitating disorders. This article provides an overview of the current standard of care for opioid use disorder and stimulant use disorder. New and emerging neuromodulation approaches with a particular focus on deep brain stimulation are then discussed.